A disposable sensor for assessing artocarpus heterophyllus l. (jackfruit) maturity - Yap, Maxsim Mee Sim; Mohd Noor, Ahmad, Prof. Dr.; Ali Yeon, Md Shakaff, Prof. Dr.; Chang, Pek Ju; Chang, Chew Cheen (MDPI, 2011)
Link to publisher's homepage at https://www.mdpi.org/